PERANGKAT PEMBELAJARAN BERBASIS LITERASI STATISTIS PADA MATERI STATISTIK - Umi Nur Qomariyah; Ririn Febrianti (Prosiding Conference on Research and Community Services, 2019)
This research is a Research and  Development, which is focused on statistical literacy-based learning tools for statistical material in elementary students. This study aims to produce literacy-based learning devices in statistical material. The subjects are fifth grade elementary school students. The stages of development of this research use a 4-D development model that has been modified to define, design and develop. Learning devices consist of lesson plans, student worksheets, teaching and learning media and student achievement tests. The research instruments used were learning tool validation sheets, teacher activity sheets, student activity sheets, student response questionnaires and student achievement tests. The results of these instruments were analyzed descriptively to answer the research objectives. The result is a literacy-based learning device in the statistical material of elementary school class V students that has been valid. Because the learning device has been revised based on validation, and after the experiment in the classroom produces the ability of the teacher to manage the class effectively, student activity is good, student responses to learning devices are positive and valid, sensitivity and reliability. Categories of achievement tests. This teaching and learning tool can be used by teachers to teach statistics to develop student statistical thinking.